Short-term effects of phosphate fertilizer enriched with low molecular weight organic acids on phosphorus release kinetic and availability under calcareous conditions in arid region - Mihoub, Adil; Bouhoun, Mustapha Daddi; NAEEM, A. (Journal of Scientific Agriculture, 2018)
Phosphate reactions and retention in the soil are of paramount importance from the perspective of plant nutrition and fertilizer use efficiency. The objective of this work was to investigate the effect of some low molecular weight organic acids (LMWOAs) on phosphorus release kinetic and its availability in calcareous soil. Experiments were conducted in laboratory. Soil-limestone mixtures were prepared to achieve highly calcareous samples (i.e. 50% CaCO3). The prepared samples were mixed thoroughly with phosphate fertilizers i.e. Triple super phosphate (TSP) and Monoammonium Phosphate (MAP) and watered with distilled water only (CK), with citric acid solution (CA) and with oxalic acid solution (OA). The treatments were arranged in a CRD with three replications and incubated at 25 ± 2°C and 80% soil moisture for a period of 960 h. The parabolic model was used for describing the decrease in P with time. As a result, all treatments showed a significant decrease in available P with time. Using LMWOAs showed important results and combination of phosphate fertilizers with both LMWOAs solutions exerted a very favorable effect on P availability in soil. The parabolic diffusion equation used was fitted well to experimental data. Addition of LMWOAs decreased loss in extractability of P with increasing soil available phosphorus fraction. Moreover, treatments irrigated by LMWOAs solutions released a lot of phosphorus compared to untreated treatments.